2004
DOI: 10.1016/j.jcrs.2003.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Changes in keratometric corneal power and refractive error after laser thermal keratoplasty

Abstract: After LTK, corneal power measured by manual keratometry was smaller than that measured by corneal topography and changes in corneal power measured by conventional keratometric instruments were greater than changes in refractive error. This difference should be considered in calculating IOL power in post-LTK eyes to prevent undesirable hyperopia after cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This difference should be considered in calculating IOL power in post-LTK eyes to prevent undesirable hyperopia after cataract surgery. 3,4 Qazi et al 5 recently demonstrated that the Orbscan II 5.00 mm total axial power and 4.00 mm total optical power can be used to more accurately predict true corneal power after myopic refractive surgery. Só nego-Krone et al 6 determined that direct measurement of central corneal optical power using Orbscan maps provides accurate post-refractive surgery corneal power, independent of historical refractive data in post-refractive surgery eyes.…”
mentioning
confidence: 99%
“…This difference should be considered in calculating IOL power in post-LTK eyes to prevent undesirable hyperopia after cataract surgery. 3,4 Qazi et al 5 recently demonstrated that the Orbscan II 5.00 mm total axial power and 4.00 mm total optical power can be used to more accurately predict true corneal power after myopic refractive surgery. Só nego-Krone et al 6 determined that direct measurement of central corneal optical power using Orbscan maps provides accurate post-refractive surgery corneal power, independent of historical refractive data in post-refractive surgery eyes.…”
mentioning
confidence: 99%